Treatment outcomes and considerations for topical immunotherapy in patients with alopecia totalis and alopecia universalis - Hitaka, Taiyo; Haruyama, Sanehito; Ohmori, Shun; Saito-Sasaki, Natsuko; Okada, Etsuko; Nakamura, Motonobu; Sawada, Yu (Frontiers in Medicine, 2025)
BackgroundAlopecia areata (AA) is a chronic immune-mediated disorder causing non-scarring hair loss. Severe forms like alopecia totalis (AT) and alopecia universalis (AU) pose therapeutic difficult situations. Topical immunotherapy with squaric acid dibutylester (SADBE) and diphenylcyclopropenone (DPCP) is widely used but has variable efficacy.ObjectivesTo evaluate the efficacy of topical immunotherapy in severe AA, identify factors influencing outcomes, and assess adjunctive antihistamine therapy.MethodsA retrospective analysis of 106 severe AA cases (26 AT, 80 AU) among 1,098 patients diagnosed between 2007 and 2016. Treatment efficacy was assessed using the Alopecia Areata Investigational Assessment Guidelines (AAIAG), and statistical analyses included chi-square tests and Kaplan-Meier analysis.ResultsAmong the 106 patients included in this study, 43% exhibited excellent or good responses to topical immunotherapy, while 75% experienced at least partial hair regrowth. Patients with alopecia totalis demonstrated slightly better outcomes than those with alopecia universalis (50% vs. 40% achieving excellent or good responses). Atopic dermatitis was significantly associated with lower treatment efficacy (54% vs. 80%, p = 0.0157). Although antihistamine use showed a trend toward improved responses (78% vs. 38%), the difference did not reach statistical significance (p = 0.0991), and multivariate analysis did not confirm its efficacy (p = 0.649). Hair regrowth was observed within 4 months in 90% of cases, while peak therapeutic effects were achieved within 3 years. Long-term treatment adherence correlated with improved outcomes, highlighting the importance of sustained therapy.ConclusionTopical immunotherapy remains an effective treatment for severe alopecia areata, although response rates vary among patients. Individualized treatment approaches, including prolonged therapy and consideration of patient-specific factors, are essential for optimizing clinical outcomes.